Prevalence of death by Covid-19 in ICU in the age group from 0 to 19 years of Roraima state - Bomfim, Laudineia Barros da Costa (2022)
Objectives: To analyze the epidemiological indicators of children and adolescents affected by COVID-19 in children and adolescents in the state of Roraima – RR and to describe the profile of deaths and the lethality of the severe acute respiratory syndrome (SARS) by COVID-19 in children and adolescents March 2020 to June 2021. Methods: Cross-sectional study from secondary epidemiological data that has as data the deaths by COVID-19 in the state of Roraima, using indicators such as many deaths, age, sex, race, and color, collected from information from the epidemiological Bulletin accessed on 06/21/2021, deaths that occurred in the Intensive care Unit. Results: Na analysis of the indicators was carried out through the data available at the SOURCE: https://roraimacontraocorona.rr.gov.br/transparencia/ Gerenciador de Ambiente Laboratorial/GAL- LACEN/ RR E SUS notifica/ministério da saúde. Conclusion: The study showed that the age group most lethally affected by COVID – 19 was 1 to 4 years old with a rate of 46.2% and that indigenous children are more vulnerable to the disease and consequently died with a rate of 51.3%.